2022
DOI: 10.1097/md.0000000000030356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enterovirus 71 vaccination on the epidemiological characteristics and etiology in hospitalized children with hand-foot-and-mouth disease: A retrospective study from a tertiary children’s hospital

Abstract: Enterovirus 71 (EV71) vaccine for hand-foot-and-mouth disease (HFMD) prevention has been available for several years. However, as a new vaccine, the impact of EV71 vaccination on the epidemiology and etiology of HFMD is currently unclear. The purpose of this study was to compare and analyze the changes of epidemiological characteristics and etiology of HFMD patients after the introduction of EV71 vaccine. The data of hospitalized children with HFMD from 2014 to 2020 were collected from the case record departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The proportion of severe cases decreased significantly after vaccination, but EV71 was still a major pathogen in patients with severe HFMD. The authors concluded that enhanced surveillance for other enteroviruses, as well as the development of a multivalent vaccine with broader protection for HFMD, is still required [57]. There are other two inactivated EV71 vaccines approved in China.…”
Section: Vaccinesmentioning
confidence: 99%
“…The proportion of severe cases decreased significantly after vaccination, but EV71 was still a major pathogen in patients with severe HFMD. The authors concluded that enhanced surveillance for other enteroviruses, as well as the development of a multivalent vaccine with broader protection for HFMD, is still required [57]. There are other two inactivated EV71 vaccines approved in China.…”
Section: Vaccinesmentioning
confidence: 99%
“…Enterovirus 71 (EV71) is the main pathogen causing hand, foot, and mouth disease (HFMD). 1 Since 1997, HFMD has emerged as a serious childhood infection in the Asia-Pacific region. 2 From 2008 to July 2022, up to 26.1 million cases of HFMD and 3727 deaths had been reported in China.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Although the main manifestations of HFMD are low-grade fever, maculopapular or papular blistering rash on the hands, feet, and mouth ulcers, 4 there were growing evidences that a large number of patients with HFMD have atypical presentations, especially those infected with the EV71, and may rapidly develop serious complications such as encephalitis, pulmonary edema, and myocarditis. 5 , 6 With the use of EV71 vaccine, 1 , 7 severe HFMD cases had significantly decreased in China. 8 However, vaccination does not completely prevent viral infection, and some children who were vaccinated may still be infected and develop complications such as encephalitis.…”
Section: Introductionmentioning
confidence: 99%
“…EV71 has caused large epidemics in southeast Asia and has been a serious health hazard in many Asian and pacific island countries [15 ▪▪ ]. One study done in Anhui China showed that a new and improved EV71 vaccine has increased efficacy and it efficient at preventing serious illness due to hand foot and mouth disease [16 ▪ ].…”
Section: Introductionmentioning
confidence: 99%